Examining lead blood levels among Ilam\'s general population in 1402 - Shahin Shahbazi; Maryam Ahmadi; Aliashraf Mozafari (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Research on blood lead levels is crucial to reduce its societal burden and assess its health effects, as lead significantly impacts cognitive function and public health. This study was designed to determine the blood lead concentration of people who have a healthy appearance. Materials & Methods: The study is cross-sectional and consists of 143 individuals selected using a random sampling from the companions of patients visiting diagnostic-therapeutic clinics in Ilam City. A gastroenterologist visited individuals to ensure they met the study inclusion and exclusion criteria. Atomic absorption spectroscopy was used to determine the serum lead levels of the participants through the collection of blood samples. The results were analyzed using analytical tests in Stata V.12 at the level of significance less than 0.05. Results: The average amount of lead present in the study sample was 9.24 μg/dl, which ranged from 1 to 86.10 μg/dl. About 70.63% of the people had serum lead levels below 10 μg/dl, while 29.37% had levels that were equal to or above 10 μg/dl. There was a significant difference in serum lead level between men (10.92 μg/dl) and women (7.54 μg/dl) (P< 0.01). The increase in serum lead levels was found to be significant in industrial workers, with a higher level than in office or domestic occupations (P= 0.02). In addition, there was no significant association between age and serum lead level. Conclusion: Ilam city's population groups are having lead serum levels higher than the permitted limit, which requires urgent measures to control and reduce pollution.